2022
DOI: 10.1038/s41467-022-30842-2
|View full text |Cite
|
Sign up to set email alerts
|

Low level of anthropization linked to harsh vertebrate biodiversity declines in Amazonia

Abstract: Assessing the impact of human activity on ecosystems often links local biodiversity to disturbances measured within the same locality. However, remote disturbances may also affect local biodiversity. Here, we used environmental DNA metabarcoding to evaluate the relationships between vertebrate biodiversity (fish and mammals) and disturbance intensity in two Amazonian rivers. Measurements of anthropic disturbance -here forest cover losses- were made from the immediate vicinity of the biodiversity sampling sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 69 publications
(100 reference statements)
0
37
0
Order By: Relevance
“…Although deforestation was used as a proxy for anthropogenic disturbances including gold mining, logging, agriculture and human settlements, gold mining remains the main cause of deforestation in the Northern Amazonian region (Dezécache et al, 2017). Within the studied area, gold mining accounts for more than 40% of the deforested surfaces (Cantera, Coutant, et al, 2022). Gold mining generates both physical and ecotoxicological impacts by releasing pollutants in the water (mercury or cyanide), degrading the riverbed and the banks and altering the water's physicochemistry (Gallay et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although deforestation was used as a proxy for anthropogenic disturbances including gold mining, logging, agriculture and human settlements, gold mining remains the main cause of deforestation in the Northern Amazonian region (Dezécache et al, 2017). Within the studied area, gold mining accounts for more than 40% of the deforested surfaces (Cantera, Coutant, et al, 2022). Gold mining generates both physical and ecotoxicological impacts by releasing pollutants in the water (mercury or cyanide), degrading the riverbed and the banks and altering the water's physicochemistry (Gallay et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The performance of the ‘teleo’ primer pair has been investigated by Polanco et al (2021), who showed that it can efficiently discriminate fish species of the Maroni River, the river with the highest species richness in French Guiana. The ‘teleo’ primer has thus been used in previous studies focused on French Guianese fish fauna (Cantera, Coutant, et al, 2022; Cantera, Decotte, et al, 2022; Cantera et al, 2019; Cilleros et al, 2019). The DNA amplifications were performed in a final volume of 25 μl containing 1 U AmpliTaq Gold DNA Polymerase (Applied Biosystems), 0.2 μM of each primer, 10 mM Tris‐HCl, 50 mM KCl, 2.5 mM MgCl 2 , 0.2 mM of each dNTP and 3 μl DNA template.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 113 out of 194 (c. 58.2%) of the carcasses had their identi cation corrected or improved (i.e., reaching higher taxonomic accuracy; Table 2 SI). In total, 173 (c. 89.2%) samples were identi ed to the species level, accounting for a nal number of 43 DNA-based species distributed into Carnivora (12), Rodentia (9), Cetartiodactyla (9), Primates (4), Eulipotyphla (1), Glires (2), Hyracoidea (2), Tubulidentata (1), Pholidota (1), and Proboscidea (1). Six morpho-species could not be identi ed because of (i) the non-resolutive power of mtDNA (large-spotted genets: Genetta pardina or G. "maculata"; cats: Felis silvestris or F. catus), (ii) among-gene con icting identities (antelope: Kobus spp.…”
Section: Resultsmentioning
confidence: 99%
“…The relative contributions of BM and TMM to hunting pressure and the connections that may link the two co-existing markets have rarely been investigated (Buij et al, 2016). Beyond the strict number of species and their volumes (taxonomic diversity and biomass), one way of assessing the potential impact of human activities on biodiversity and ecosystems is to quantify trends in the diversity of functional traits, namely functional diversity (FD) (Cantera et al, 2022;Su et al, 2021). Predicting the long-term in uence of wildlife trade on the FD of ecosystems remains challenging, but a few studies from the tropical forests have already demonstrated that reduced mammalian densities could lead to signi cant ecosystem changes and cascading effects along the food chain (Tagg et al, 2020).…”
Section: Introductionmentioning
confidence: 99%